SEMANTIC RELATIONS OF SUCCESS-RELATED WORDS: MEANING COMPONENT ANALYSIS - Athriyana Pattiwael (LINGUISTIKA, 2018)
One of the contributions of the study in Semantics area is conducting studies that focus on the meaning relation among lexical choices. The result contributes in providing information related to the appropriate choice of lexical in its context. This is also the interest and focus of this paper. Basing itself on Nida’s framework (1975), this paper covers the discussion and the analysis of the meaning relations among success-related words namely accomplishment, achievement, attainment, victory, triumph and fulfillment.